ANALISIS PENGGUNAAN MEDIA SOSIAL DALAM PENGEMBANGAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) - Lailatus Sa’adah; Ita Rahmawati; Siti Afiyah (Economicus : Jurnal Ekonomi dan Manajemen, 2021)
In an increasingly sophisticated era, the development of technology has made major changes in the business world. One of them is on social media which is increasingly developing and facilitating communication. Communication in business is very important. So it is necessary to achieve the existing conveniences and need to be used as well as possible. This form of utilization can be accepted by MSME actors in Indonesia, especially MSMEs in Jombang District. By using the interview method to thoroughly discuss the use of social media in their business, and using supporting questions, the results of the study show that the use of social media can be made to facilitate media promotion, so as to improve the development of MSMEs themselves. The sales rate is getting faster and automatically increases in other aspects of the business. The increase that occurred has made MSME players feel benefited and facilitated by the current sophistication of technology. The positive benefits obtained by MSME players are expanding market networks, facilitating interaction with consumers, and increasing product sales.